Фізіолого-біохімічні особливості інтродукованих видів та сортів роду Hemerocallis L. - Shcherbakova, T.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
A review of current trends of physiological and biochemical studies of Hemerocallis L. are presented. The new data about taxonomy and phylogeny, introduction, the genetic basis of plant breeding, quantitative and qualitative analysis of pigments, and biology of flowering, identification and рhysiological action of biologically active substances are given.